Currency Value Changes: Historical Dynamics and Islamic Legal Perspectives in Maqāṣid Ash-Shari’ah: Perubahan Nilai Mata Uang: Dinamika Sejarah dan Hukum Islam dalam Perspektif Maqāṣid Asy-Syari’ah - Darussalam, Ishlahu; Muhammad, Izbik (Sharia and Law Faculty of Sunan Kalijaga Islamic State University Yogyakarta, 2024)
Abstract: This article discusses the fluctuations in currency value throughout the history of Islamic economics, from a precious metal-based monetary system (gold and silver) to the adoption of paper money. It also examines scholars' perspectives on the legal status of paper money and the challenges faced by contemporary monetary systems, including inflation and usury (riba). Employing a qualitative approach, this study analyzes historical literature and Islamic jurisprudence related to changes in the monetary system and the issues posed by fiat currencies. The data were primarily gathered through a review of various scholarly opinions on paper money, which are expected to provide a foundation for developing a more stable monetary system in line with Shariah principles. The study finds that the transition from a metal-based monetary system (gold and silver) to paper money introduces challenges related to inflation and riba, which contradict the principles of Maqāṣid Ash-Sharī’ah. Therefore, the study emphasizes the need for a more stable monetary policy aligned with Shariah principles, suggesting technology-based solutions such as asset-backed currencies or cryptocurrency as more stable alternatives free from exploitative debt practices classified as riba. Abstrak: Artikel ini membahas fluktuasi nilai mata uang sepanjang sejarah ekonomi Islam, mulai dari sistem moneter berbasis logam mulia (emas dan perak) hingga adopsi uang kertas. Artikel ini juga mengkaji pandangan para ulama mengenai status hukum uang kertas serta tantangan yang dihadapi oleh sistem moneter kontemporer, termasuk inflasi dan riba (bunga). Menggunakan pendekatan kualitatif, studi ini menganalisis literatur sejarah dan fiqih Islam terkait perubahan sistem moneter dan masalah yang ditimbulkan oleh mata uang fiat. Data utama dikumpulkan melalui tinjauan berbagai pendapat ulama tentang uang kertas, yang diharapkan dapat menjadi landasan untuk mengembangkan sistem moneter yang lebih stabil sesuai dengan prinsip-prinsip Syariah. Studi ini menemukan bahwa transisi dari sistem moneter berbasis logam (emas dan perak) ke uang kertas menimbulkan tantangan terkait inflasi dan riba, yang bertentangan dengan prinsip-prinsip Maqāṣid Ash-Sharī’ah. Oleh karena itu, studi ini menekankan perlunya kebijakan moneter yang lebih stabil sesuai dengan prinsip-prinsip Syariah, dengan mengusulkan solusi berbasis teknologi seperti mata uang yang didukung aset atau cryptocurrency sebagai alternatif yang lebih stabil dan bebas dari praktik utang eksploitatif yang diklasifikasikan sebagai riba.